$4.50 you just do 18/4 to get ur answer per hour
The expression x( x - 4 ) when expanded is x² - 4x
An expression, often known as a mathematical expression, is a finite collection of symbols that are well-formed in accordance with context-dependent principles.
When a bracket is expanded, each term is multiplied by the expression outside of the bracket.
The distributive property states that multiplying the sum of two or more addends by a number yields the same outcome as multiplying each addend separately by the number and combining the resulting products.
Consider the expression,
x( x - 4 )
Let us assume y = x( x - 4 )
Using the distributive property, a( b + c ) = ab + ac
y = x( x - 4 )
y = x · x - x · 4
y = x² - 4x
Therefore, x( x - 4 ) = x² - 4x
Therefore, the expression when expanded is x² - 4x.
Learn more about expression here:
brainly.com/question/1859113
#SPJ1
Answer: diameter = 2R = 28
Circumference = 2pieR
= 28pie
= 87.964594300514
Step-by-step explanation:
I used a calculator for this..
Answer:
4x -2y + 8z
Step-by-step explanation:
10 / 4 = 4x
-5y / 2.5 = -2y
20z / 2.5 = 8z
resulting in 4x -2y + 8z.
Answer:
30in^3
Step-by-step explanation:
3x1^2x10=
3x1x10=
30
30in^3